If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2x-9=2x-13
We move all terms to the left:
2x-9-(2x-13)=0
We get rid of parentheses
2x-2x+13-9=0
We add all the numbers together, and all the variables
4!=0
There is no solution for this equation
| 19-(6x)=49 | | 21 n+16=4+43 n | | 9k+1=-9+7k | | -8/7=7u | | -4+9t=9t-4 | | 112=2(w+11) | | 2x-3=2+5x | | 3x+2+2x=35 | | 10(x+3)^2+80=0 | | p/16+1=2 | | -4(-5x+5)=-100 | | 8x-90=2x-35 | | 25x-7-17x+2=19x-7-11x+12 | | 5(2x-21)=215 | | .1/7x=-8 | | 3x-7+5=13 | | y=-6^2+2 | | 3x-3-9=-16x-8-x | | 5(y+4)=-7 | | 2x+4+5=21 | | 2y+3y+10=90 | | 187=253-x | | 15x+10=44 | | 5x-2(x+7)=-5+2x+1 | | –4p+6=–7p−1−8 | | 2161(3x)=1000 | | 0.25x-5=0.75-12 | | 1+3h10=h | | 2(x-4)-2=4 | | 13(d+1)=13 | | y=4^2+5 | | 10(x-7)-6x=10(8x-4) |